PENGARUH PENGGUNAAN TEKNIK COGNITIVE MODELLING TERHADAP KEMAMPUAN BERBICARA ANAK DIDIK GUGUS PAUD 8 KECAMATAN GADANG KOTA MALANG - Ayu Asmah; Romia Hari Susanti, (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2020)
Speaking is an ability to produce articulation sounds to express or to tell ideas, thought, and feeling. In a case of children speech disorder, it is a complicated problem faced by the children and their parents. The aim of this research is to study effect of the use of Cognitive Modelling Technique to children speaking ability of Early Childhood Education Group 8 in Gadang Sub-District Malang. The research method of this study is Quasi Experimental Design by using Pre-test pattern and Post-test Group. The used of Cognitive Modelling Technique is effective to improve children speaking ability of Early Childhood Education Group 8 in Gadang Sub- District Malang. It is based on hypothesis test result which shows probability below 0.05 (0.0025 <0.05), the result means that Ho is rejected